Subcostal versus transhepatic view to assess the inferior vena cava in critically ill patients. Issue 8 (5th August 2020) - Valette, Xavier; Ribstein, Pierre; Ramakers, Michel; du Cheyron, Damien
Abstract: Background: Evaluation of the inferior vena cava (IVC) is not always possible through the subcostal (SC) window. Methods: Inferior vena cava diameters measured by transhepatic (TH) and SC views were compared by Bland and Altman analysis. Results: 131 patients were enrolled, including 88 (67%) under mechanical ventilation. The echogenicity was statistically poorer through the TH view in comparison with the SC view ( P  = .002). The correlation between the SC and TH views was good and better for respiratory variation than for end‐expiratory or end‐inspiratory diameter measurements ( r  = 0.86). Despite low bias, the limits of agreement were wide (−7.5 and 7.7 mm for end‐expiratory diameter, −8.7 and 8.5 mm for end‐inspiratory diameter, and −5.3 and 5.8 mm for respiratory variation). Complementary analysis showed that the concordance between the SC and the TH views was better when the IVC was distended. However, the limits of agreement remained broad. Conclusions: Although feasible in almost all patients, the TH view does not provide better echogenicity in comparison with the SC view. Despite a good correlation with the SC view and a low bias, the limits of agreement were wide, especially when the IVC has an ellipsoidal shape, suggesting caution in the interpretation of data obtained by the TH view.